2013
DOI: 10.1074/jbc.m113.473827
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchyme-specific Knockout of ESET Histone Methyltransferase Causes Ectopic Hypertrophy and Terminal Differentiation of Articular Chondrocytes

Abstract: Background: Articular chondrocytes are responsible for producing articular cartilage and do not normally enter into terminal differentiation. Results: Conditional knock-out of ESET histone methyltransferase results in hypertrophy, apoptosis, and terminal differentiation of articular chondrocytes. Conclusion: ESET is essential for the normal maintenance of articular cartilage and joint function in adult animals. Significance: Learning regulatory mechanisms of articular chondrocytes is critical to the understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In growth plate chondrocytes, ESET associates with HDAC4 to suppress Runx2 activity and hypertrophy; thus, ESET‐deficient chondrocytes undergo accelerated hypertrophy. Interestingly, the authors also saw increased ectopic hypertrophic differentiation of articular chondrocytes (Lawson et al, ; Yang et al, ), a feature of OA as discussed below. A second histone methyltransferase, DOT1L, was recently identified as another potential regulator of chondrocyte differentiation in a genome‐wide association study (GWAS) for hip OA susceptibility loci (Castano Betancourt et al, ; Evangelou et al, ), but detailed studies on the role of this gene in chondrocyte differentiation are required.…”
Section: Regulation Of Chondrocyte Hypertrophymentioning
confidence: 95%
See 1 more Smart Citation
“…In growth plate chondrocytes, ESET associates with HDAC4 to suppress Runx2 activity and hypertrophy; thus, ESET‐deficient chondrocytes undergo accelerated hypertrophy. Interestingly, the authors also saw increased ectopic hypertrophic differentiation of articular chondrocytes (Lawson et al, ; Yang et al, ), a feature of OA as discussed below. A second histone methyltransferase, DOT1L, was recently identified as another potential regulator of chondrocyte differentiation in a genome‐wide association study (GWAS) for hip OA susceptibility loci (Castano Betancourt et al, ; Evangelou et al, ), but detailed studies on the role of this gene in chondrocyte differentiation are required.…”
Section: Regulation Of Chondrocyte Hypertrophymentioning
confidence: 95%
“…In addition to acetylation, many other posttranslational modifications control histone and nucleosome function, but very few of these have been studied in the context of chondrocyte differentiation. Two recent studies have demonstrated a role for the histone methyltransferase ESET in hypertrophy (Lawson et al, ; Yang et al, ). In growth plate chondrocytes, ESET associates with HDAC4 to suppress Runx2 activity and hypertrophy; thus, ESET‐deficient chondrocytes undergo accelerated hypertrophy.…”
Section: Regulation Of Chondrocyte Hypertrophymentioning
confidence: 99%
“…ESET, a H3K9-specific histone methyltransferase also called Set domain protein bifurcated 1 (SETDB1), is transiently upregulated in prehypertrophic chondrocytes in newborn mice. ESET controls hypertrophic differentiation of growth plate chondrocytes and formation of epiphyseal plates (80) , as well as the terminal differentiation of articular chondrocytes (81) . ESET conditional deletion in mesenchymal cells causes acceleration of chondrocyte hypertrophy during embryonic and prenatal development, resulting in a defect in long bone growth and trabecular bone formation.…”
Section: Histone Methylationmentioning
confidence: 99%
“…Herlofsen et al have demonstrated that the methylation level of H3K4me3 and H3K36me3 is largely associated with chondrocyte differentiation of human mesenchymal stem cells, assessed by Chip-Seq analysis [64]. Setdb1 (SET domain, bifurcated1) regulates chondrocyte hypertrophy by inhibiting Runx2 activity through H3K9 methylation [65,66]. However, despite its significance in gene expression pathways, only the role of histone acetylation has been predominantly studied in chondrogenesis, with little attention given to the regulatory mechanism of histone methylation/demethylation during chondrocyte differentiation.…”
Section: Histone Methylationmentioning
confidence: 98%